Análise estatística para detecção de regularidades em eleições brasileiras - Silva, Leandro Magno Correa da (2020)
Using statistical concepts and tools, this work was aimed at understanding how the electorate participated in the polling stations in the last 5 Brazilian presidential elections, comparing them and obtaining regularities and anomalies in the distribution of votes and attendance. There were no indications of fraud mechanisms, reinforcing the fragility of the fraud thesis in Brazilian elections. Clear regularity was observed between elections electing candidates from the ruling party and more irregular behavior in the 2018 election.